A Thermotolerant Variant of Rubisco Activase From a Wild Relative Improves Growth and Seed Yield in Rice Under Heat Stress - Scafaro, Andrew P.; Atwell, Brian J.; Muylaert, Steven; Reusel, Brecht Van; Ruiz, Guillermo Alguacil; Rie, Jeroen Van; Gallé, Alexander (Frontiers in Plant Science, 2018)
Genes encoding thermostable variants of the photosynthesis heat-labile protein Rubisco activase (Rca) from a wild relative Oryza australiensis were overexpressed in domesticated rice (Oryza sativa). Proteomics was used to quantify the abundance of O. australiensis Rca (Rca-Oa) in the resulting plants. Plants were grown to maturity in growth rooms and from early tillering until immediately prior to anthesis, they were exposed to daytime maximum temperatures of 28, 40 and 45°C and constant night temperatures of 22°C. Non-destructive measurements of leaf elongation and photosynthesis were used to compare the null segregant with a transfected line in which 19% of its total Rca content was the recombinant O. australiensis Rca (T-Oa-19). Height, fresh mass, panicle number, seed set and seed number were measured at final harvest. Traits at maturity after heat stress at 45°C correlated strongly with recombinant protein abundance. Seed number was far the most responsive trait to an increase in Rca-Oa abundance, improving by up to 150%. Leaf elongation rates and tiller number were significantly greater in the transformed plants in the first two weeks of exposure to 45°C but tiller numbers later became equal in the two genotypes. Gas exchange measurements showed that T-Oa-19 had faster light induction of photosynthesis but not significantly higher CO2 assimilation rates, indicating that the carbon gain that resulted in large yield improvement after growth at 45°C was not strongly correlated with an instantaneous measurement of steady-state photosynthesis. When plants were grown at 40°C daytime maximum, there was no improvement in the final biomass, panicle or seed number when compared with 28°C, indicating that the threshold for heat damage and beneficial effects of the thermostable Rca recombinant protein was between 40°C and 45°C, which corresponded to leaf temperatures in the range 38 - 42°C. The results suggest that the thermotolerant form of Rca from O. australiensis was sufficient to enhance carbohydrate accumulation and storage by rice over the life of the plant, dramatically improving yields after exposure to heat throughout the vegetative phase.